Litigation Versus Legislation: The Emerging Role of State Attorneys General as National Policymakers - Ketterer, Andrew (Maine Policy Review, 2001)
In the Margaret Chase Smith Essay, Andrew Ketterer, who served three terms as Maine‘s Attorney General, discusses the increasingly important role of state attorneys general in influencing policy. This has come about to an extent because of multi-state lawsuits, such as the landmark national suit against tobacco companies.
Keywords: state attorneys general